Models of participatory budgeting. Analysis of participatory budgeting procedures in Poland - Mączka, Krzysztof; Jeran, Agnieszka; Matczak, Piotr; Milewicz, Maciej; Allegretti, Giovanni (Polskie Towarzystwo Socjologiczne, 2021)
This paper presents a study on participatory budgeting in Poland, analyzing participatory budgetingprocedures. We apply the typology of participation models proposed by Sintomer, and based on the previousresearch we investigate which model of participatory budgeting is characteristic for Poland. This study covered49 cases of participatory budgeting implementation in Western Poland, mainly in the Wielkopolska Province andthe neighboring provinces. The results show that none of the municipalities covered by the study had a relativelypure participatory budgeting model, as proposed by Sintomer. The procedures in the analyzed municipalities canbe characterized as the patchwork participatory budgeting model.
Keywords: public consultations; public participation; public policies; decision making